Characterization of a halophilic heterotrophic nitrification–aerobic denitrification bacterium and its application on treatment of saline wastewater. (March 2015) - Duan, Jinming; Fang, Hongda; Su, Bing; Chen, Jinfang; Lin, Jinmei
Highlights: Halophilic Vibrio diabolicus SF16 was isolated from marine sediment. It had good heterotrophic nitrifying–aerobic denitrifying ability at high salinity. It could utilize ammonium to generate primarily inert N2 rather than N2 O. Strain SF16 improved nitrogen removal efficiency in the biological reactor system. Abstract: A novel halophilic bacterium capable of heterotrophic nitrification–aerobic denitrification was isolated from marine sediments and identified as Vibrio diabolicus SF16. It had ability to remove 91.82% of NH4 + -N (119.77 mg/L) and 99.71% of NO3 − -N (136.43 mg/L). The nitrogen balance showed that 35.83% of initial NH4 + -N (119.77 mg/L) was changed to intracellular nitrogen, and 53.98% of the initial NH4 + -N was converted to gaseous denitrification products. The existence of napA gene further proved the aerobic denitrification ability of strain SF16. The optimum culture conditions were salinity 1–5%, sodium acetate as carbon source, C/N 10, and pH 7.5–9.5. When an aerated biological filter system inoculated with strain SF16 was employed to treat saline wastewater, the average removal efficiency of NH4 + -N and TN reached 97.14% and 73.92%, respectively, indicating great potential of strain SF16 for future full-scale applications.